Creating web pages for dummies® ebook - Smith, Bud E. (Dummies., 2009)
It’s easy to design, build, and post a Web page with Google Page Creator or CoffeeCup HTML Editor, but a friendly guide still comes in handy. Creating Web Pages For Dummies®, 9th Edition introduces you to Web design software and online page-building tools, and walks you through the process in record time. Like its previous editions, this book gives you the skinny on getting Web pages up and running with the least amount of hassle. But not just ho-hum Web pages! Yours will look fantastic and be easy to build, and you’ll even get a trial version of CoffeeCup HTML Editor and visual design tools on the bonus CD. You’ll learn to: Get a simple page designed and online by the end of Chapter 3 Optimize photos, video, and audio for the Web and get them onto your page Register for a Google account and use the versatile Google Page Creator Build pages using basic HTML or CoffeeCup HTML Editor Identify and apply elements of design, avoid common errors, and create pages that get noticed Maintain control by creating and editing pages in HTML with a text editor Understand how image file size affects your pages, how to upload photos to Flickr, and how to add sound and video files to your Web pages Develop your pages into a site with CoffeeCup HTML Editor and Visual Editor You’ll even find out more about blogging and Blogger.com. The trial software on the CD is for Windows, but the instructions for building great Web pages work on any system! Note: CD-ROM/DVD and other supplementary materials are not included as part of eBook file.